2021
DOI: 10.3390/rs13081428
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Optimised Hyperspectral Remote Sensing Retrieves Cotton Nitrogen Status

Abstract: Hyperspectral imaging spectrometers mounted on unmanned aerial vehicle (UAV) can capture high spatial and spectral resolution to provide cotton crop nitrogen status for precision agriculture. The aim of this research was to explore machine learning use with hyperspectral datacubes over agricultural fields. Hyperspectral imagery was collected over a mature cotton crop, which had high spatial (~5.2 cm) and spectral (5 nm) resolution over the spectral range 475–925 nm that allowed discrimination of individual cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Research has indicated that the spectral characteristics of plant canopy reflections are closely related to several biochemical and biophysical properties, such as pigment concentrations [ 31 , 32 ], plant vigor [ 33 , 34 ], water status [ 35 , 36 ], and nutritional status [ 37 , 38 ]. Different nitrogen states in cotton cause reflectance changes in multiple bands of the spectrum, such as 550–700 nm [ 39 ], 705–715 nm [ 40 ], and 1325–1575 nm [ 41 ]. Hyperspectral remote sensing plays an important role in plant nitrogen nutrition monitoring as a cutting–edge technology.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that the spectral characteristics of plant canopy reflections are closely related to several biochemical and biophysical properties, such as pigment concentrations [ 31 , 32 ], plant vigor [ 33 , 34 ], water status [ 35 , 36 ], and nutritional status [ 37 , 38 ]. Different nitrogen states in cotton cause reflectance changes in multiple bands of the spectrum, such as 550–700 nm [ 39 ], 705–715 nm [ 40 ], and 1325–1575 nm [ 41 ]. Hyperspectral remote sensing plays an important role in plant nitrogen nutrition monitoring as a cutting–edge technology.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that N, P, and K contents and accumulation could provide a reliable evaluation of the crop growth conditions and yield predictions [11,12]. Several studies have used unmanned aerial vehicles, satellite remote sensing [13][14][15], machine vision, and neural networks to monitor the nutritional status of crops [16,17]. However, the above studies mainly focused on the methods and platforms without considering that the different nutrient distribution leads to different cotton yields.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning can be used to estimate nitrogen levels on crop leaves using satellite imagery by collecting data, extracting relevant features, training a machine learning model, and validating the model. Marang et al (2021) proposed hybrid random forest regression, DBSCAN, and PCA to predict N level on cotton crop using hyperspectral UAV and sentinel imagery. Huang et al (2015) estimated rice nitrogen status based on satellite imagery.…”
Section: Introductionmentioning
confidence: 99%